2016
DOI: 10.1096/fj.201500030r
|View full text |Cite
|
Sign up to set email alerts
|

GPR41 modulates insulin secretion and gene expression in pancreatic β‐cells and modifies metabolic homeostasis in fed and fasting states

Abstract: Insulin secretion by pancreatic β-cells is primarily regulated by glucose; however, hormones and additional nutrients, such as long-chain fatty acids, also play an important role in adjusting insulin output to physiologic needs. To examine the role of short-chain fatty acids (SCFAs) in β-cell function, we analyzed mouse models of gain and loss of function of GPR41 (FFAR3), a receptor for SCFAs, vs. wild-type control mice. GPR41 gain of function [GPR41-overexpressing transgenic (41 Tg) model] and GPR41 loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 30 publications
8
76
2
1
Order By: Relevance
“…Total RNA from single-cell suspensions or snap-frozen skin, liver, colon or ileum was isolated using the miRNeasy Kit (Qiagen) and reverse transcribed into cDNA using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Foster City, CA). The following primers and PowerUP SYBR green polymerase (Applied Biosystems) were used to detect the following transcripts: 5′-CACGGCCTACATCCTCATCT-3′ and 5′-TTGGTAGGTACCAGCGGAAG-3′ ( Gpr43 ); 5′-CTGGCGGAGCTACGTGCT-3′ and 5′-GGGGTCGATACAAGAGT-3′ ( Gpr41 ) 43 ; 5′-ATGGCGAGGCATATCTGTGTAGCA-3′ and 5′-TCCTGCCTGAGCAGAACAAGATGA-3′ ( Gpr109a ) 44 ; 5′-GTCAACCGCACCTTTATGCT-3′ and 5′-GAACAGTTTCTCCCCGATGA-3′ ( IL-22 ); and 5′-TGACCTCAACTACATGGTCTACA-3′ and 5′-CTTCCCATTCTCGGCCTTG-3′ ( Gapdh ) 45 . All reactions were performed according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA from single-cell suspensions or snap-frozen skin, liver, colon or ileum was isolated using the miRNeasy Kit (Qiagen) and reverse transcribed into cDNA using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Foster City, CA). The following primers and PowerUP SYBR green polymerase (Applied Biosystems) were used to detect the following transcripts: 5′-CACGGCCTACATCCTCATCT-3′ and 5′-TTGGTAGGTACCAGCGGAAG-3′ ( Gpr43 ); 5′-CTGGCGGAGCTACGTGCT-3′ and 5′-GGGGTCGATACAAGAGT-3′ ( Gpr41 ) 43 ; 5′-ATGGCGAGGCATATCTGTGTAGCA-3′ and 5′-TCCTGCCTGAGCAGAACAAGATGA-3′ ( Gpr109a ) 44 ; 5′-GTCAACCGCACCTTTATGCT-3′ and 5′-GAACAGTTTCTCCCCGATGA-3′ ( IL-22 ); and 5′-TGACCTCAACTACATGGTCTACA-3′ and 5′-CTTCCCATTCTCGGCCTTG-3′ ( Gapdh ) 45 . All reactions were performed according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, it is noted that butyrate, as a potent inhibitor of histone acetyltransferase and deacetylases (HDACs), epigenetically induces the proliferation and differentiation of immune cells [37] and upregulates the adiponectin-mediated AMPK pathway that stimulates mitochondria biogenesis and fatty acid oxidation [38]. In addition, the SCFA-induced GPR41/GPR43 signaling was reported to be capable of directly acting on pancreatic β cells to regulate insulin secretion [39,40,41,42]. For example, McNeils et al [40] demonstrated in vitro the enhancement of glucose-stimulated insulin secretion and β cell proliferation and gene expression by treating the isolated β cells with a GPR43-specific agonist.…”
Section: Dietary Fiber-derived Short Chain Fatty Acids and Obesitymentioning
confidence: 99%
“…Stimulates leptin production in adipocytes [154]. Modulates insulin secretion in pancreas [155] Gpr43 (FFAR2) SCFA (acetate, propionate,…”
Section: Butyrate)mentioning
confidence: 99%